Competition with Exclusive Contracts in Vertically Related Markets: An Equilibrium Non-Existence Result - Nicolas Schutz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
I develop a model in the spirit of Ordover, Saloner, and Salop (1990), in which two upstream firms compete to supply a homogeneous input to two downstream firms, who compete in prices with differentiated products in a downstream market. Upstream firms are allowed to offer exclusive two-part tariff contracts to the downstream firms. I show that, under very general conditions, this game does not have a subgame-perfect equilibrium in pure strategies. The intuition is that variable parts in such an equilibrium would have to be pairwise-proof. But when variable parts are pairwise-proof, downstream competitive externalities are not internalized, and there exists a profitable deviation. I contrast this non-existence result with earlier papers that found equilibria in similar models.
urn:nbn:de:bvb:19-epub-17398-5
Keywords: 330